The Extent of Ventilator-Induced Lung Injury in Mice Partly Depends on Duration of Mechanical Ventilation - Maria A. Hegeman; Sabrine N. T. Hemmes; Maria T. Kuipers; Lieuwe D. J. Bos; Geartsje Jongsma; Joris J. T. H. Roelofs; Koenraad F. van der Sluijs; Nicole P. Juffermans; Margreeth B. Vroom; Marcus J. Schultz (Critical Care Research and Practice)
Background. Mechanical ventilation (MV) has the potential to initiate ventilator-induced lung injury (VILI). The pathogenesis of VILI has been primarily studied in animal models using more or less injurious ventilator settings. However, we speculate that duration of MV also influences severity and character of VILI. Methods. Sixty-four healthy C57Bl/6 mice were mechanically ventilated for 5 or 12 hours, using lower tidal volumes with positive end-expiratory pressure (PEEP) or higher tidal volumes without PEEP. Fifteen nonventilated mice served as controls. Results. All animals remained hemodynamically stable and survived MV protocols. In both MV groups, PaO2 to FiO2 ratios were lower and alveolar cell counts were higher after 12 hours of MV compared to 5 hours. Alveolar-capillary permeability was increased after 12 hours compared to 5 hours, although differences did not reach statistical significance. Lung levels of inflammatory mediators did not further increase over time. Only in mice ventilated with increased strain, lung compliance declined and wet to dry ratio increased after 12 hours of MV compared to 5 hours. Conclusions. Deleterious effects of MV are partly dependent on its duration. Even lower tidal volumes with PEEP may initiate aspects of VILI after 12 hours of MV.